HIV transmission, public health detention and the recalcitrant subject of discipline: Kuoth, Lam v R and the co-constitution of public health and criminal law. Issue 2 (2nd April 2016) - Carter, David J.
ABSTRACT: The attempt to govern HIV through technologies of coercion, compulsion or detention has long raised significant questions for law, public health and state practice generally. In this vein, many public health writers have challenged the continued availability of criminal-legal sanction in relation to particular HIV-related events, namely where potential or actual transmission might result in constraint or deprivation of liberty by virtue of criminal punishment. Within public health practice, however, a variety of communicable disease approaches utilise the same technologies of constraint or deprivation of liberty, including administrative detention. As yet, the structural and operational connections between criminal legal and public health practices have not been adequately addressed. Here I read the recent case of Kuoth, Lam v R [2010] VSCA 103 (21 April 2010) as an event that disturbs the dominant frame of separation and difference that we have applied to the relationship between public health and criminal law. To do so, I draw principally upon the work of Foucault and his recent interpreters, Ben Golder and Peter Fitzpatrick. As I shall argue, despite a disjunction between these two powers of modernity, the operation of criminal law and public health are not at odds, but are rather mutually co-constitutive.